Are SRI funds conventional funds in disguise or do they live up to their name? - Christin Nitsche; Michael Schröder (Zentrum für Europäische Wirtschaftsforschung (ZEW), 2015)
In recent years, the socially responsible investing (SRI) industry has become an important segment of international capital markets by incorporating ESG (Environmental, Social and Governance) factors into investment selection and management processes. This study analyses whether SRI mutual funds are conventional funds in disguise or invest in line with their ESG objectives. In contrast to other studies, the analysis exclusively focuses on the non-financial performance of SRI vis-à-vis conventional funds and applies ESG corporate ratings of three rating agencies (Oekom, Sustainalytics and ASSET4) to a European and global fund universe. The SRI and non-SRI funds are analyzed with respect to differences in their Top 10 fund holdings, their average ESG rankings and the significance of rating differences by utilizing cross-sectional regressions. At a first glance, the top holdings of both fund types seem very similar, but the results of the ranking analysis show that SRI funds have on average higher ESG rankings. Additionally, the cross-sectional regressions show that the ESG rating differences between SRI funds and conventional funds are significantly positive, i.e. SRI funds exhibit higher ESG ratings than conventional funds. These findings are robust as they hold for every single ESG factor and total scores and as well as across the different ratings applied.
urn:nbn:de:bsz:180-madoc-389150
Keywords: G11; G23; G24; M14; 330; Mutual funds; socially responsible investments; ESG performance; ESG ratings